2015
DOI: 10.1111/jep.12301
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the implementation process of clinical pathways: a mixed method study within the context of Swedish intensive care

Abstract: Bottom-up initiatives, interprofessional project groups and small ICUs seem to enhance successful implementation of CPs while inadequate electronic health record systems, insufficient support and time constrains can be barriers. Support regarding the whole implementation process from centralized units at the local hospitals, as well as cooperation between ICUs and national guidance, has the potential to raise the quality of CPs and benefit the progress of CP implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 40 publications
3
22
0
1
Order By: Relevance
“…How the effect of a standardised care plan is evaluated can have a profound effect on its perceived usefulness (Bjurling-Sjöberg et al, 2015). Therefore when undertaking such research it is important to ensure robust methods and data analysis are adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the effect of a standardised care plan is evaluated can have a profound effect on its perceived usefulness (Bjurling-Sjöberg et al, 2015). Therefore when undertaking such research it is important to ensure robust methods and data analysis are adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Without structured guidelines ICU nurses over-rely on doctors for decision making when caring for dying patients (Venkatasalu et al, 2015). Bjurling-Sjöberg et al (2015) suggested that a reason for doctor's reluctance to use standardised care plans is the perception that they lose control over decision making. Further research could identify other significant factors affecting implementation and compliance.…”
Section: Implementation and Compliancementioning
confidence: 99%
“…Key persons from those ICUs have witnessed a positive impact of the pathways, such as a better care structure, better quality control and easier documentation. They have also pointed out that the implementation process is complicated and is affect by multiple factors, such as inspiration sources, the project group constellation, available resources, pathway characteristics, implementation activities, and staff characteristics [ 23 ]. The study that revealed these findings was, however, retrospective and primarily included the people responsible for pathway implementation, which, in some cases, had occurred several years ago [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have also pointed out that the implementation process is complicated and is affect by multiple factors, such as inspiration sources, the project group constellation, available resources, pathway characteristics, implementation activities, and staff characteristics [ 23 ]. The study that revealed these findings was, however, retrospective and primarily included the people responsible for pathway implementation, which, in some cases, had occurred several years ago [ 23 ]. Although the key informants’ perspectives provided valuable insights to facilitate enhanced pathway use and further understand the implementation process, there was a need for more knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In altre parole, la gran parte delle LG non fornisce elementi per l'appropriatezza organizzativa inerente la loro implementazione. Si sono, comunque, valutati i Fattori Critici di Successo nell'implementazione dei PDTA [17,18], seppure con esiti contraddittori. Tuttavia, si possono indicare, nell'ordine: consapevolezza del top management, consapevolezza e iniziativa bottom-up dei professionisti, sistemi di accreditamento, feedback (miglioramento continuo), capacità manageriali, sistema informativo, comunicazione, aderenza al PDTA (mantenimento), consapevolezza dei pazienti.…”
Section: Percorsi Diagnostico-terapeutici Assistenziali (Pdta)unclassified